The real school safety problem: the long-term consequences of harsh school punishment - Kupchik, Aaron (University of California Press, 2016)
Introduction -- Effective school crime prevention -- Extending inequality -- Hurting families / with Thomas Mowen -- How schools teach bullying / with Katie A. Farina -- Civic participation in the future / with Thomas Catlaw -- Financial costs of school security and punishment -- Conclusion